MINYAK ESSENSIAL PADA KEMANGI (Ocimum basilicum L.) - Dr. Marina Silalahi, M.Si (Jurnal Pro-Life, 2018)
Ocimum basilicum L. or basil is widely used as a community producing the essential oils. By human the Ocimum basilicum has been used as medicine, vegetable, and spices. This article is based on offline and online media literature. Offline literature used the books, disertations, thesis, whereas online media used Web, Scopus, Pubmed, and scientific journals. The main essential oils in the Ocimum basilicum have monotherpene derivatives (camphor, limonene, 1,8-cineole, linalool, geraniol) and phenylpropanoid derivatives (eugenol, methyleugenol, chavicol, estragole, methyl-cinnamate). The traditional medicine its utilized as a carminative, stomach and antispasmodial, nausea, bloating, and dysentery. Based on its, bioessay have activity as an antioxidant, anti-bacterial, and anti-cancer. Keywords: Ocimum basilicum, essential oils, anti-cancer, and anti-bacterial